Co-infusion of donor adipose tissue-derived mesenchymal and hematopoietic stem cells helps safe minimization of immunosuppression in renal transplantation – single center experience. (October 2014) - Vanikar, Aruna V.; Trivedi, Hargovind L.; Kumar, Ashutosh; Gopal, Saroj Chooramani; Patel, Himanshu V.; Gumber, Manoj R.; Kute, Vivek B.; Shah, Pankaj R.; Dave, Shruti D.
Abstract Background: Stem cell therapy (SCT) is used for immunosuppression minimization in renal transplantation (RT). We carried out a prospective study to evaluate the benefits of co-infusion of donor adipose-derived mesenchymal stem cells (AD-MSC) + hematopoietic stem cells (HSC) in living donor RT (LDRT) under non-myeloablative conditioning. Methods: In a demographically balanced three-armed LDRT trial with 95 patients in each arm, group-1 received portal co-infusion of AD-MSC + HSC, group-2 received HSC and group-3 received no SCT. Lymphoid irradiation and anti-thyroglobulin were used for conditioning. Results: SCT was safe. At 1 and 5 years post-transplant, patient survival was 100% and 94.7% in group-1, 100% and 95.7% in group-2, and 94.7% and 84% in group-3, death-censored graft survival was 100% and 94.6% in group-1, 100% and 91.3% in group-2, and 98.9% and 94.4% in group-3 with mean serum creatinine (mg/dL) of 1.38 and 1.39 in group-1, 1.48 and 1.51 in group-2, and 1.29 and 1.42 and in group-3. Rejection episodes and immunosuppression requirement were lesser in SCT groups versus controls with best results noted in group-1. Conclusion: Coinfusion of donor AD-MSC +HSC in portal circulation pre-transplant under non-myeloablative conditioning is safe and effective for immunosuppression minimization in LDRT.